Meditation and Religion: Buddhist Practice and Islamic Contemplative Analogues - Nubail, Ahmad; Arrazy, Lazuardi Fadhlan; Sultani, Zul Fadhli; Syihabuddin, Haydar (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
This paper examines meditation, a practice that has become a global trend and is increasingly promoted as a therapeutic intervention in health-related contexts. This development has contributed to a shift in the public perception of meditation—from a religious tradition to a medicalized instrument—potentially detaching it from its original spiritual and religious meanings. Accordingly, this study explores meditation in Buddhism as its primary focus and discusses Islamic traditions as a comparative perspective. By clarifying key terms and conceptual meanings, the paper identifies both convergences and divergences between Buddhist meditation and selected Islamic practices, particularly within Sufism. It also addresses a recurring controversy in public discourse, namely the claim that “there is no meditation in Islam,” while acknowledging that the two religions are not treated as equivalent or interchangeable frameworks.